Periodic Solution for Nonlinear Second Order Differential Equation System - Hojeen M. Haji, Raad N. Butris, Hezha H. Abdulkareem, Dlovan H. Omar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
In this work, we investigate the periodic solutions for non-linear system of differential equations by using the method of periodic solutions of ordinary differential equations which are given by A.M.Samoilenko. Additionally, the existence and uniqueness theorem have been proved for second differential equations system by using Banach fixed point theorem